STRATEGI BAURAN PEMASARAN USAHA ROTI MAROS SALENRANG DI KABUPATEN MAROS, PROVINSI SULAWESI SELATAN - KURNIA,; MARHAWATI,; MUSTARI,; MUHAMMAD HASAN,; MUHAMMAD DINAR, (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
This study aims to determine and analyze the marketing mix strategy of the Maros Salenrang Bread Business in Maros Regency, South Sulawesi Province. The research method used is a qualitative descriptive research approach using data collection methods through observation, interviews and documentation of the research object, which is then analyzed using SWOT analysis. Based on the results of the research shows that the strategy adopted by the Maros Salenrang Bread Business is in accordance with the SWOT analysis in quadrant I, which is an aggressive strategy with the application of a strategy (growth oriented strategy) which is a very profitable situation with the application of a marketing mix policy, so this strategy is expected increase growth and achieve maximum business progress.